Strategi Branding Dan Digital Marketing Pada UMKM Untuk Membangun Identitas Brand Di Desa Nglebak - Ayu Oktavianingrum; Dwi Nur Hidayati; Ertien Rining Nawangsari (Lembaga Pengembangan Kinerja Dosen, 2023)
The development of the times and technology demands that many people be able to balance in the realm of work, such as UMKM. In its development, it is required to introduce and market its products more easily and modernly. This is what gave rise to the term